Expression and significance of mammalian target of rapamycin in cutaneous squamous cell carcinoma and precancerous lesions. Issue 2 (20th December 2021) - Xu, Gongjun; Fang, Jinxian; Xu, Jinlun; Shen, Zhen; Huang, Chiqing; Jiang, Yixiu
ABSTRACT: The aim of this study is to explore the role of mammalian target of rapamycin (mTOR) in cutaneous squamous cell carcinoma (CSCC), Bowen's disease (BD), and actinic keratosis (AK) with squamous cell differentiation abnormality and its relationship with the degree of tumor proliferation. Thirty cases of clinical paraffin specimens of CSCC, BD, and AK were each collected from Jinhua Fifth Hospital, while 30 cases of normal skin specimens surgically resected in Department of Plastic Surgery were selected as controls. The expressions of mTOR and Ki-67 in tissues were detected by immunohistochemical staining. The positive expression rate of mTOR in the CSCC group was higher than those in the BD group and AK group ( P < 0.05), while it was higher in the BD group and AK group than in the normal skin group ( P < 0.05). The CSCC group had a higher positive expression rate of Ki-67 than the AK group ( P < 0.01). The results of logistic regression analysis showed that the pathogenic site [odds ratio (OR) = 1.189, 95% confidence interval (95%CI): 1.028–1.381, P = 0.021], course of disease (OR = 2.059, 95%CI: 1.036–4.087, P = 0.043), and differentiation degree (OR = 1.325, 95%CI: 1.169–1.512, P = 0.001) were independent factors for the positive expression of mTOR. OR>1, indicating that the factor is a risk factor. The expression levels of mTOR in CSCC, BD, and AK were positively correlated with the expression level of Ki-67 ( r = 0.827, P < 0.01, r = 0.608, P < 0.01, r = 0.368, P = 0.045). These results suggest that mTOR may be involved in the pathogenesis of CSCC, and related to the proliferation degree of CSCC, as an index reflecting the proliferation status of CSCC.